The Dataset Finder: A Tool Utilizing Data Management Plans as a Key to Data Discoverability - Soo-Yon Kim; Steffen Hillemacher; Max Kocher; Bernhard Rumpe; Sandra Geisler (Data Science Journal)
In the past years, there has been an increased interest in sharing and reusing research data. While the importance of sharing data is urgent for enabling collaboration, many research projects are currently struggling with setting up a strategy and the right infrastructure for enabling such data-driven collaboration among the project’s researchers. Through an analysis of the Cluster of Excellence project Internet of Production as a use case, we have found that to enable researchers to share and find research data, a suitable platform is needed, as well as processes that smoothly blend into existing research data management practices. We argue that leveraging data management plans from a medium of documentation to a dynamic knowledge source enhances overview and discoverability of data, while integrating easily into day-to-day workflows of researchers. We present a tool, the Dataset Finder, which is built on the basis of data management plans, and allows users to intuitively query available datasets. The current functionalities of the tools are discussed, results of a preliminary evaluation, as well as potential future features.